Pelatihan Dasar Pembuatan Website Online Shop di SMA Negeri 2 Mawasangka Tengah Desa Watorumbe Bata - Anindita, Faradisa; Wiana; Warni; Widiawati; Yeni Ilva; Muh. Zulzayat Rapi (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Watorumbe Bata Village, located in Mawasangka Tengah, Buton Tengah, is home to a majority of residents working as farmers, fishermen, and weavers. Their woven products are mostly for personal use, but some are sold in local markets. The village has one high school, SMA Negeri 2 Mawasangka Tengah, equipped with advanced information technology learning facilities. These facilities enable students to acquire basic web programming skills, particularly in creating online shop websites. With the rapid growth of the digital economy, web development skills are becoming crucial for the younger generation to seize opportunities in the digital economy. This training program covers the basics of HTML, CSS, and JavaScript, along with an introduction to e-commerce concepts. Participants are trained to directly build simple yet functional online shop websites. The results show a significant improvement in students' programming abilities, highlighting the great potential of rural youth to excel in the digital field when provided with adequate resources and support. These skills are expected to help the weaving community in Watorumbe Bata Village market their products to a broader audience through digital platforms.